Branched-Chain Amino Acid Fortification Does Not Restore Muscle Protein Synthesis Rates following Ingestion of Lower- Compared with Higher-Dose Mycoprotein. Issue 11 (4th September 2020) - Monteyne, Alistair J; Coelho, Mariana O C; Porter, Craig; Abdelrahman, Doaa R; Jameson, Thomas S O; Finnigan, Tim J A; Stephens, Francis B; Dirks, Marlou L; Wall, Benjamin T
ABSTRACT: Background: We have shown that ingesting a large bolus (70 g) of the fungal-derived, whole food mycoprotein robustly stimulates muscle protein synthesis (MPS) rates. Objective: The aim of this study was to determine if a lower dose (35 g) of mycoprotein enriched with branched-chain amino acids (BCAAs) stimulates MPS to the same extent as 70 g of mycoprotein in resistance-trained young men. Methods: Nineteen men [aged 22 ± 1 y, BMI (kg/m 2 ): 25 ± 1] took part in a randomized, double-blind, parallel-group study. Participants received primed, continuous infusions of l -[ ring - 2 H5 ]phenylalanine and ingested either 70 g mycoprotein (31.5 g protein; MYCO; n = 10) or 35 g BCAA-enriched mycoprotein (18.7 g protein: matched on BCAA content; ENR; n = 9) following a bout of unilateral resistance exercise. Blood and bilateral quadriceps muscle samples were obtained before exercise and protein ingestion and during a 4-h postprandial period to assess MPS in rested and exercised muscle. Two- and 3-factor ANOVAs were used to detect differences in plasma amino acid kinetics and mixed muscle fractional synthetic rates, respectively. Results: Postprandial plasma BCAA concentrations increased more rapidly and to a larger degree in ENR compared with MYCO. MPS increased with protein ingestion ( P ≤ 0.05) but to a greater extent following MYCO (from 0.025% ± 0.006% to 0.057% ± 0.004% · h −1 in rested muscle, and from 0.024% ± 0.007% to 0.072% ± 0.005% · h −1 in exercised muscle; P < 0.0001) compared with ENR (from 0.031% ± 0.003% to 0.043% ± 0.005% · h −1 in rested muscle, and 0.027% ± 0.005% to 0.052% ± 0.005% · h −1 in exercised muscle; P < 0.01) ingestion. Postprandial MPS rates were greater in MYCO compared with ENR ( P < 0.01). Conclusions: The ingestion of lower-dose BCAA-enriched mycoprotein stimulates resting and postexercise MPS rates, but to a lesser extent compared with the ingestion of a BCAA-matched 70-g mycoprotein bolus in healthy young men. This trial was registered at clinicaltrials.gov as 660065600.